If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x-13=8x+17
We move all terms to the left:
10x-13-(8x+17)=0
We get rid of parentheses
10x-8x-17-13=0
We add all the numbers together, and all the variables
2x-30=0
We move all terms containing x to the left, all other terms to the right
2x=30
x=30/2
x=15
| 25-10(12-x)=5(2x-7) | | 216+x=x*x*x-5x+6x | | 11=x+13 | | 4x-2(x-5)=2+4x-2 | | -1/3(x−15)=−4, | | 216+x=x*x*x-5x+6 | | 2+3.y=17 | | 23x-2=5x | | 7⁄28=25⁄x | | 7=7+x+6x | | b/10=-7 | | 3(4x+4)=60 | | 4/7t+1/4=9/14t+3/2 | | 7x+3+3x+7=110 | | 9x^2-36x+12=0 | | 13=9r+8 | | 8+x=2x-1 | | -6/11x=1/5 | | 9-5r=-13-7r | | 2^2x=4 | | -102=6x | | 6=20-2x | | 16-2t=2/3+9 | | 3r+45-2=1 | | 3(s+3)^23(s+3)=8 | | 14n=11 | | s+21/2s+20s=55 | | 4-x-13=6x+7-3x | | 216+x=x(x*x-5)+6x | | -3(4f-5)=-28 | | -13=m|-15 | | 6x2+7x=3 |